Research progress of three⁃dimensional finite element analysis in unilateral maxillary defect restorations - WEI Yanan; CAO Zhiyun (口腔疾病防治, 2018)
Unilateral maxillary defects are common clinical maxillofacial deformities. Because of their large area and the complexity of the maxillary structure, the distribution of pressure from dental prostheses and on the sustentacu⁃ lar tissue is usually uneven, which often results in pain or ulceration of the soft tissue and agomphiasis during the thera⁃ peutic process. Recently, the finite element method has been used to guide prosthesis design and implantation. This method is conducive to the restoration and stability of the dental prosthesis and the protection of the remaining tissue, which improves restoration quality and patient satisfaction. This paper summarizes the establishment of a three⁃dimen⁃ sional finite element model of unilateral maxillary defects and its application in repairing unilateral maxillary defects with traditional prostheses, implant⁃supported prostheses and surgical flap transplantation combined with prostheses.